Sejl i jorden - Khankan, Nathalie (Passage - Tidsskrift for litteratur og kritik, 2009)
Nathalie Khankan: “Sails in the Soil” In standard accounts of Palestinian literature, literary expression invariably figures as national allegory, rarely explaining meaning as it is created in the text. This article problematizes the categories used by historiographers to describe Palestinian literature. It does so through the site of the so-called New 1990s Poets, whose texts upset monolithic literary narratives. At the same time these poems also help us better understand the endurance of that overriding tension in Palestinian cultural production between the political and collective pressures of the text on the one hand and more personal, subjective figurations on the other.